PENGARUH TINGKAT PENGETAHUAN PENGARUH TINGKAT PENGETAHUAN, PERAWATAN DAN EDUKASI GURU TERHADAP KESEHATAN GIGI SISWA DI SDN PAKUHAJI V KABUPATEN TANGERANG: Kesehatan Gigi, tingkat pengetahuan, perawatan dan edukasi guru - Bambang Mardi Sentosa; Ida Farida; Siti Homalia (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2021)
ABSTRACT Background: The prevalence of 2016 Global Burden of Disease Study, dental and oral health problems, especially tooth decay, are diseases that affect almost half of the world???s population (3,58 Billion people). One of the causes of dental health problems in Indonesia is the lack of knowledge, care and education of the teachers. Purpose: to find out whether there is an effect of the knowledge, care and education of the teachers toward the dental health of the students SDN Pakuhaji V Kabupaten Tangerang. Research method: this research used quantitative causal with cross sectional approach. Proportionate stratified random sampling was used to obtain 153 respondents. Result of the research: according to the T-test, the level of the knowledge had no effect toward students??? dental health, while care and education of the teachers had effect on it. Based on the result of F-test, the level of knowledge, care and education of the teachers had effect toward students??? dental health simultaneously with F- table 2,67 and sig 0,000. Conclusion: there was the effect of the level of knowledge, care and education of the teachers toward students??? dental health.